2015
DOI: 10.7862/rz.2015.mmr.11
|View full text |Cite
|
Sign up to set email alerts
|

Regional Food Products and Region-Wise Consumer Ethnocentrism

Abstract: Iwona OLENIUCH 1 Izabela CICHOCKA 2 REGIONAL FOOD PRODUCTS AND REGION-WISE CONSUMER ETHNOCENTRISM The article is an attempt to answer the question about the relationship between regional food and buyers' attitudes as well as consumer ethnocentrism phenomenon. The concept of regional products was defined by using both the definition of the labeling associated with this category in the legislation of the EU and terms used by practitioners and theoreticians concerned with food market. On the basis of a review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The literature has identified several reasons for buying domestic foods (see [108] for a review), among which the following stand out: health-related issues [11], which has caused an increase in demand for high-quality, functional, or sustainable products; paying special attention to elements related to "emotional value" [7]; and an opposition to globalization in food production, which has focused on social aspects related to sustainability [6]. This behavior relates to support of local products and "can constitute a direct response to the needs of the ethnocentric consumer" [130] (p. 149). Thus, since understanding EC levels in a market can determine the success or failure of a particular product, the appropriate use of COO identifiers can provide competitive advantages based on the product [131].…”
Section: Discussionmentioning
confidence: 99%
“…The literature has identified several reasons for buying domestic foods (see [108] for a review), among which the following stand out: health-related issues [11], which has caused an increase in demand for high-quality, functional, or sustainable products; paying special attention to elements related to "emotional value" [7]; and an opposition to globalization in food production, which has focused on social aspects related to sustainability [6]. This behavior relates to support of local products and "can constitute a direct response to the needs of the ethnocentric consumer" [130] (p. 149). Thus, since understanding EC levels in a market can determine the success or failure of a particular product, the appropriate use of COO identifiers can provide competitive advantages based on the product [131].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies (Fernández-Ferrín et al 2020;Bianchi and Mortimer 2015), have shown that consumer ethnocentrism can vary among different regions of the same country and that it has a strong influence in purchasing local or regional products, because consumers want to support local economy. This is particularly evident when consumers buy regional or local labelled products, such as Protected Designation of Origin, Protected Geographical Indications and Traditional Specialty Guaranteed (Oleniuch and Cichocka 2015) products or local sustainable fruits and vegetables (Boca 2021), because, by means of their consumption, they contribute to the sustainable development or rural areas.…”
Section: Consumer Ethnocentrism Literaturementioning
confidence: 99%